Inter-annual variability in Prosopis caldenia pod production in the Argentinean semiarid pampas: A modelling approach. (August 2016) - Risio, Lucía; Calama, Rafael; Bogino, Stella M.; Bravo, Felipe
Abstract: The driest part of the Argentinean pampas is occupied by semiarid woodlands dominates by Prosopis caldenia Burkart (Calden). Calden pods are a highly valuable fodder supplement for livestock but its production is highly variable. Our objective was to analyze and model the temporal pattern in inter-annual variability of Calden pod production. Our key hypothesis is that weather conditions are the main determinant of the pod masting behaviour. Tree size and climatic variables were evaluated as explanatory covariates using a zero-inflated log-normal modelling approach. The proposed final model structure incorporated 25 parameters, including four variance components, two intercepts for both the logistic and the log-normal parts of the model, and nineteen parameters associated with fixed effects. Climate had a strong influence on the flowering-fruiting Calden process and on the inter-annual variability of the final pod production at the tree level. Temperatures during bud breaking, flowering and fruit shedding, together with the precipitation from the final month of fruit shedding and the total amount of the prior vegetative cycle, were the main weather covariates that affect the processes. Highlights: We model the P. caldenia pod production at tree level. Zero-Inflated Log-Normal mixture distribution with random components was fitted. Climate has strong influence on the flowering-fruiting P. caldenia process. Temperatures and precipitation are the main covariates that affect the processes.